Communication Strategies Used in Teaching Media Information Literacy for Combating Hoaxes in Indonesia: A Case Study of Indonesian National Movements - Ummah, Nurul Hidayatul; Fajri, Muchamad Sholakhuddin Al (Information & Media, 2020)
This study examined communication strategies used by Indonesian national movements to teach media information literacy as an endeavour to fight hoaxes. The in-depth online interview and content analysis had been employed to investigate approaches of the movement to campaign media information literacy competence to society. The findings reveal that the offline communication has been massively applied by the movement to establish direct engagement to give a comprehensive understanding. Moreover, in the case of online communication, the content of Instagram shows that the movements predominantly use Instagram for marketing tools which post much information related to offline activities, instead of educated contents that contain media information literacy understanding. This study suggests that educating media information literacy through online communication should be prioritised, as 140 million Indonesians are active social media users, dominated by the youth aged 18-24 who are prone to be attacked by fake news.
Keywords: hoax news; media information literacy; digital media; content analysis; communication strategy; social media; Instagram